EFEKTIVITAS PEMISAHAN LAJUR SEPEDA MOTOR PADA JALAN KOLEKTOR PRIMER (FSTPT Indonesia, 2023)
a national road faces problems with the behavior of motorists, especially motorbikes that are not orderly. Motorcyclists often violate speed limits and cut off traffic movements or prepare uncharacteristically. So the purpose of this study is to analyze traffic characteristics in existing conditions and simulated scenarios in order to increase LOS and an analysis is carried out based on the graph of the Greenshields method. In scenario 1, the condition of the road section describes the condition of the road section by adding complete and dotted double markers. While the condition of scenario 2 describes the condition of the road segment by making additional lanes specifically for motorcycles. The result of the traffic service level of the two scenarios, scenario 2 gets a better LOS value. Based on the graph of the Greenshields method, the two scenarios have the same result, which is in the uncongested area for each traffic characteristic relationship. The best traffic characteristics in uncongested area conditions are in scenario 2. ABSTRAK Jalan Nasional memiliki masalah dari perilaku pengendara khususnya sepeda motor yang tidak tertib. Pengemudi sepeda motor sering melanggar batas kecepatan dan memotong pergerakan lalu lintas atau menyiap dengan tidak umum. Sehingga tujuan dari penelitian ini untuk menganalisis karakteristik lalu lintas pada kondisi eksisting dan skenario yang disimulasikan agar meningkatkan LOS serta dilakukan analisis berdasarkan grafik metode Greenshields. Pada kondisi skenario 1 menggambarkan kondisi ruas jalan dengan menambahkan marka ganda utuh dan putus - putus. Sedangkan kondisi skenario 2 menggambarkan kondisi ruas jalan dengan membuat lajur tambahan khusus sepeda motor. Hasil dari tingkat pelayanan lalu lintas kedua skenario, skenario 2 mendapatkan nilai LOS yang lebih baik. Berdasarkan grafik metode Greenshields kedua skenario memiliki hasil yang sama yaitu berada pada kondisi uncongested area setiap hubungan karakteristik lalu lintasnya. Karakteristik lalu lintas terbaik dalam kondisi uncongested area berada pada skenario 2.